2010
DOI: 10.1371/journal.pone.0013219
|View full text |Cite
|
Sign up to set email alerts
|

Differential Genetic Regulation of Canine Hip Dysplasia and Osteoarthritis

Abstract: BackgroundCanine hip dysplasia (HD) is a common polygenic trait characterized by hip malformation that results in osteoarthritis (OA). The condition in dogs is very similar to developmental dysplasia of the human hip which also leads to OA.Methodology/Principal FindingsA total of 721 dogs, including both an association and linkage population, were genotyped. The association population included 8 pure breeds (Labrador retriever, Greyhounds, German Shepherd, Newfoundland, Golden retriever, Rottweiler, Border Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 73 publications
1
54
1
2
Order By: Relevance
“…With the availability of sequencing technology and high-density whole genome single nucleotide polymorphism (SNP) canine mapping arrays, the associated markers and critical genes underpinning HD and ED will be identified [29], [30]. The molecular genetic information could be combined into a selection scheme to increase the accuracy and lower the incidence of disease more rapidly, and likely more effectively, than that based on EBVs alone [31][34].…”
Section: Discussionmentioning
confidence: 99%
“…With the availability of sequencing technology and high-density whole genome single nucleotide polymorphism (SNP) canine mapping arrays, the associated markers and critical genes underpinning HD and ED will be identified [29], [30]. The molecular genetic information could be combined into a selection scheme to increase the accuracy and lower the incidence of disease more rapidly, and likely more effectively, than that based on EBVs alone [31][34].…”
Section: Discussionmentioning
confidence: 99%
“…FN1 had been proposed to have a function in matrix organization of cartilage [32]. In an across-breed GWAS, EVC and EVC2 on CFA3, PTPRD on CFA11 and MFAP1 on CFA30 were suggested as CHD candidate genes [12]. All these genes are highly expressed in cartilage and mutations in these genes can cause chondrodysplasia ( EVC , EVC2 ), Marfan syndrome ( MFAP1 ) or restless legs syndrome ( PTPRD ) [12].…”
Section: Discussionmentioning
confidence: 99%
“…A genome-wide association study (GWAS) for CHD and osteoarthritis (OA) across several dog breeds including Labrador Retriever-Greyhound crosses identified four CHD-associated and two OA-associated SNPs. The CHD-associated SNPs were located on CFA3, 11 and 30 [12], but not within QTL of the Labrador Retriever-Greyhound crossbred linkage study [8]. In 174 Bernese Mountain Dogs, two different CHD-regions were identified on CFA14.…”
Section: Introductionmentioning
confidence: 93%
“…The PON2 and FN1 genes were hypothesised to be part of the pathogenesis of CHD due to their involvement with bone mineral density and extracellular matrix in cartilage respectively (Pfahler and Distl 2012). Four SNP associated with CHD and two SNP loci associated with hip osteoarthritis have also been identified in a separate study (Zhou et al 2010). Friedenberg et al (2011) identified an association between a mutation-deletion haplotype in the candidate gene, fibrillin-2 gene (FBN2) and CHD.…”
Section: The Genetic Basis Of Chdmentioning
confidence: 99%
“…Whilst current DNA marker technology is not yet sufficiently refined to be used in the selection of breeding animals, DNA marker information acquired via such means may be available to breeders in the future (Marschall and Distl 2007;Zhu et al 2008;Zhou et al 2010 Genomic selection also allows breeding selection to be carried out earlier because the DNA tests can be performed on animals at a younger age. More importantly, genomic estimated breeding values distinguish between littermates, thereby minimising the rate of inbreeding.…”
Section: The Genetic Basis Of Chdmentioning
confidence: 99%